Magnetic and electronic properties of diamond-shaped graphene-boron nitride nanoribbons and nanoflakes. (December 2019) - Guerra, T.; Araújo, L.R.S.; Azevedo, S.
Abstract: New and interesting physical phenomena arise in ultra-small materials, such as nanoribbons and nanoflakes. Such structures have properties that are significantly modified by the width, type and shape of the edge, size and composition. These diverse possibilities to control them, makes some types of nanoribbons and nanoflakes are not fully understood so far. Here, we study diamond-shaped graphene-boron nitride nanoribbons and nanoflakes using density functional theory. We investigate the structural, magnetic and electronic properties as functions of variable widths along nanoribbon and the lateral size of the nanoflakes. We find that boron nitride structures with predominantly zigzag edges are more stable than graphene systems with such edges. Magnetic moment in graphene-boron nitride nanoflakes is directly proportional to the difference between the number of carbon atoms in each sublattice. We observed giant magnetic moments by supercell (approximately 5 μ B ). The n × n supercell of the diamond-shaped graphene-boron nitride nanoflakes has a magnetic moment n μ B . Variable width, 1-D and 2-D quantum confinement can adjust the properties of nanoribbons and nanoflakes. Highlights: Boron nitride structures with predominantly zigzag edges are more stable than graphene systems with such edges. The n x n supercell of the diamond-shaped graphene-boron nitride nanoflakes has a magnetic moment n μ B. Variable width, 1-D and 2-D quantum confinement can adjust the properties of nanoribbons and nanoflakes.